The Influence of Organizational Culture, Work Environment, and Work Discipline on Employee Performance at the Department of Population and Civil Registration of Bandung City - Rendi Karyadi; Nina Karlina; M.D. Enjat Munajat (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of organizational culture, work environment, and work discipline on employee performance at the Population and Civil Registration Office of Bandung City. This study uses primary and secondary data. This study used 60 respondents with a simple random sampling method, where researchers took random samples from employees of the Population and Civil Registration Office of Bandung City. The data analysis technique used in this study is analysis with the PLS-SEM model using SMARTPLS 4.0.9.9 software. The results of the data analysis show that organizational culture has a positive and strong relationship with employee performance, as well as the work environment and work discipline, which significantly affect employee performance. Meanwhile, organizational culture and work environment have a positive and strong relationship with work discipline at the Population and Civil Registration Office of Bandung City. The findings in this study indicate that organizational culture, work environment, and work discipline are related and mutually influence employee performance in an organization.